Tentoonstelling actuele beeldende kunst. - Debruyne, Johan; Van Acker, Olivier; Vanduyver, Bart (Brugge : Cultureel Centrum Brugge, 2020)
Bernolet, Ignace ; Aertsen, Simon ; Arreaza, Rosángela ; Calmeyn, Nancy ; Cools, Lotte ; De Vlamynck, Erica ; De Wolf, Matthias ; De Zutter, Sarah ; Deceuninck, Tim Theo ; Delaere, Lucas ; Demey, Kathleen ; Devriendt, Ruth ; Ghyselen, Jonas ; Godderis, Sien ; Lamoot, Raven ; Lombaert, Walter ; Mareel, Line ; Puype, Sylvie ; Roelant, Sammy ; Simoens, Peter ; Six, Johan ; Van den Berghe, Sophie ; Van Dycke, Bruno ; Vanderschoot, Alice ; Verle, Frieke ; Werniers, Roselynd
SANT2020. Tentoonstelling actuele beeldende kunst, Hendrik Pickeryzaal, Belfort, Brugge, 06.09.2020 - 11.10.2020
boek